2014
DOI: 10.1002/etc.2536
|View full text |Cite
|
Sign up to set email alerts
|

Degradation rate of sodium fluoroacetate in three New Zealand soils

Abstract: The degradation rate of sodium fluoroacetate (SFA) was assessed in a laboratory microcosm study incorporating 3 New Zealand soil types under different temperature (5 °C, 10 °C, or 20 °C) and soil moisture (35% or 60% water holding capacity) conditions using guideline 307 from the Organisation for Economic Co-operation and Development. A combination of nonlabeled and radiolabeled (14) C-SFA was added to soil microcosms, with sampling and analysis protocols for soil, soil extracts, and evolved CO(2) established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Aerial control has been underpinned by extensive research aimed at increasing percentage kills of such operations, and reducing per hectare costs, as well as addressing non-target and welfare impacts, user safety and ensuring operational reliability. Other research has aimed to gain a better understanding of, and address public concerns related to, the impacts of 1080 on the environment and possible residues in water (Eason et al 2011 ; Northcott et al 2014 ).…”
Section: Operational Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerial control has been underpinned by extensive research aimed at increasing percentage kills of such operations, and reducing per hectare costs, as well as addressing non-target and welfare impacts, user safety and ensuring operational reliability. Other research has aimed to gain a better understanding of, and address public concerns related to, the impacts of 1080 on the environment and possible residues in water (Eason et al 2011 ; Northcott et al 2014 ).…”
Section: Operational Practicesmentioning
confidence: 99%
“…Other research has investigated the fate of 1080 in the environment once it has been deployed in bait form, assuming it has not been consumed by a pest, and shown that 1080 can leach from baits (Suren 2006 ), but that it is readily degraded in soils at ground temperatures over 5°C (Northcott et al 2014 ). Further, of the 1080 that typically leaches from baits following rain, less than 1% is subsequently found in surface water where it could feasibly pose a risk for terrestrial animals (Srinivasan et al 2012 ).…”
Section: Operational Practicesmentioning
confidence: 99%
“…The reaction scheme is shown in Figure . Extraction and derivatization were performed at Landcare Research (Lincoln, New Zealand) using the method of Northcott et al The chemical derivatives were delivered to the Otago University Chemistry Department Stable Isotope Laboratory and measured as received. The aliquots of the reagents used by Landcare were supplied to Otago and used for subsequent derivatization.…”
Section: Methodsmentioning
confidence: 99%
“…For many fluoro-organics biodegradation is completely unknown. Monofluorinated compounds like fluorophenols [7][8][9][10], fluorobenzenes [11][12][13][14][15], fluorobenzoates [16][17][18], fluoroanilines [19][20][21], and fluoroacetate (FA) [22][23][24] are more likely to be biodegraded, while polyfluorinated compounds are more prone to be recalcitrant, as is the case with perfluorinated compounds. [1,25,26] In contrast to the countless number of man-made fluorinated molecules, fluorine is rarely found in natural compounds, in spite of constituting the 13th most abundant element on Earth.…”
Section: Introductionmentioning
confidence: 99%